Handling and Publishing Wireless Sensor Network Data: a hands-on experiment - Koga, Ivo K.; Medeiros, Claudia Bauzer; Branquinho, Omar (Anais do Brazilian e-Science Workshop (BreSci); 2010: Anais do IV e-Science Workshop, 2010)
eScience research, in computer science, concerns the development of tools, models and techniques to help scientists from other domains to develop their own research. One problem which is common to all is concerned with management of heterogeneous data offering multiple interaction possibilities. This paper presents a proposal to help solve this problem, tailored to wireless sensor data – an important data source in eScience. This proposal is illustrated with a case study.